Political economy of reforms and liberalisation achievements, failures and future policy issues - Mahajan, V. S., ed. (Deep & Deep Publications New Delhi, 1997)
|
Keywords: India--Economic policy; Economic development--India -- Economic forecasting--India; Central planning--India